Pediatric Off-Label COVID-19 Vaccination: The Concerns of Healthcare Professionals in Pakistan - Sadia Shakeel; Shagufta Nesar; Ghazala Noor Nizami; Zafar Iqbal; Shaista Emad; Quratulain Wasim; Tayyaba Mumtaz; Shazia Jamshed; Muhammad Salahuddin Usmani; Rabia Hussain (Vaccines, 2022)
Global health authorities have emphasized the vital role of healthcare professionals (HCPs) as a reliable source of vaccination information for patients in primary care. However, HCPs are concerned whether COVID-19 vaccinations can be used off-label. Hence, the current study was conducted to assess their perspectives towards off-label COVID-19 immunization in children. The study tool, consisting of 40 items, was utilized to evaluate HCPs’ knowledge and attitudes towards the off-label use of the COVID-19 vaccine in children under 12 years of age. To assess the unfavorable attitudes regarding vaccinations, the Vaccination Attitudes Examination Scale was employed. Overall, 477 completed questionnaires were incorporated in the present study, with a response rate of 88.9%. The mean age of the respondents was 38.6 ± 7.5 years; among whom the majority were physicians, n = 209 (43.8%), and pharmacists, n = 112 (23.4%). Approximately 78% of the respondents had a general awareness of off-label vaccination. Around 80% knew the adverse drug reactions associated with the use of COVID-19 vaccines. Females showed more mistrust about vaccine benefits, n = 55 (16.9%), compared to males, n = 21 (13.8%), and concerns about commercial profits of vaccines, n = 59 (18.1%), compared to males, n = 19 (12.5%). By profession, physicians showed statistically significantly lower mistrust, n = 18 (8.6%), and higher concerns about unpredicted effects of vaccines, n = 41 (19.6%). A major portion of the respondents, n = 327 (68.5%), did not consider that HCPs should prescribe/administer off-label COVID-19 vaccination in children. The current findings demonstrated that respondents had an appropriate level of understanding about COVID-19 immunization in children. They showed higher levels of rejection for off-label use of the COVID-19 vaccination.